The Aesthetic Necessity Of "Design Codes" In The Use Of Cultural Heritage Objects - N. Abdujalilova; N.S. Buronov; S.M. Usmanov (Genius Journals, 2024)
The paper considers the review of some architectural objects of the old town part of Samarkand formed by the end of the XIV-th first half of the XV-th countries. The destruction of the domes and minarets led to the disappearance of these unique architectural qualities of the Ulugbek madrasah. Additional studies, undertaken in connection with the planned restoration revealed a number of data on the history of the construction of the madrasah, helped to understand some features of its architecture, to establish the initial purpose of separate premises. We made a thorough examination of the entrance opening in the western wall of the aivan, which gave every reason to support the opinion of the previous researchers. The opening is distorted in shape, it is located not exactly along the axis, it is not coordinated with the composition of the framing facing it. In the development of the design-code of the historical regions of Bukhara, the analysis of the architectural style of the city and the national elements of the building facades are discussed. The state of the hotel business and its construction processes, the processes of combining national style and modernity in hotels, and the formation of the new "Bukhara style" are discussed. In addition, there is information about the research to identify local materials in the development of city design code rules.
Keywords: reconstruction; architecture; design code; heritage